Job Satisfaction Model of Primary Health Care Midwives Based on Indonesian Workforce Research in the Health Sector - Despitasari, Mieska; Bachtiar, Adang; Hendarwan, Harimat; Besral, Besral; Yuniar, Yuyun (UI Scholars Hub, 2023)
Promotive, preventive, curative, and rehabilitative efforts that are comprehensive, integrated, and sustainable are employed to enhance the health state of the global population. Within this context, however, the quality of primary health care depends on job satisfaction, which leads to the happiness of human resources in the health sector. Therefore, this study aimed to analyze and formulate a job satisfaction model among primary health care midwives in Indonesia. This study was an advanced secondary data analysis of a cross-sectional study conducted in 2017 by the National Institute of Health Research and Development, Ministry of Health of the Republic of Indonesia. A total of 87,341 midwives from all 9,669 primary health cares in Indonesia participated in this study. Data were collected by distributing the Minnesota Satisfaction Questionnaire, elaborating on the satisfaction level and relevant contributing factors. The prefilled Likert scale questionnaire was analyzed using logistic regression. The findings suggested a model indicating that motivation, work area (region), history of salary delay, and training received were important for their job satisfaction, whereas the motivation aspect contributed the most. Therefore, the local and central governments must consider these factors in the human resource policymaking process.